2016
DOI: 10.1088/1475-7516/2016/11/023
|View full text |Cite
|
Sign up to set email alerts
|

Towards the quantization of Eddington-inspired-Born-Infeld theory

Abstract: Abstract. The quantum effects close to the classical big rip singularity within the Eddingtoninspired-Born-Infeld theory (EiBI) are investigated through quantum geometrodynamics. It is the first time that this approach is applied to a modified theory constructed upon Palatini formalism. The Wheeler-DeWitt (WDW) equation is obtained and solved based on an alternative action proposed in Ref.[1], under two different factor ordering choices. This action is dynamically equivalent to the original EiBI action while i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 106 publications
1
50
0
Order By: Relevance
“…The classical singular asymptotic behaviour of these dark energy models has led to a quantum cosmological analysis of these setups [39][40][41][42]95]. In these works, it was concluded that once the Universe enters in a genuinely quantum phase; i.e., where coherence and entanglement effects are important, the Universe would evade a doomsdayà la rip.…”
Section: Introductionmentioning
confidence: 99%
“…The classical singular asymptotic behaviour of these dark energy models has led to a quantum cosmological analysis of these setups [39][40][41][42]95]. In these works, it was concluded that once the Universe enters in a genuinely quantum phase; i.e., where coherence and entanglement effects are important, the Universe would evade a doomsdayà la rip.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in [29], this can be reached by considering an alternative action which is dynamically equivalent to the action (10):…”
Section: Quantum Cosmology Of the Big Rip Model Within The Eddington-mentioning
confidence: 99%
“…Classically, these actions are dynamically equivalent. Starting from the action (13) and inserting the FLRW ansatz, we can obtain the Lagrangian of this model in which the matter field is described by a perfect fluid (see Reference [29])…”
Section: Quantum Cosmology Of the Big Rip Model Within The Eddington-mentioning
confidence: 99%
See 1 more Smart Citation
“…An attractive candidate is the EiBI theory [3]. This theory has been widely investigated both from the cosmological and astrophysical points of view [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The EiBI theory is able to cure the big bang singularity at the cosmological level [19].…”
Section: Introductionmentioning
confidence: 99%